C5 nephritic factors drive the biological phenotype of C3 glomerulopathies - Marinozzi, Maria-Chiara; Chauvet, Sophie; Le Quintrec, Moglie; Mignotet, Morgane; Petitprez, Florent; Legendre, Christophe; Cailliez, Mathilde; Deschenes, Georges; Fischbach, Michel; Karras, Alexandre; Nobili, Francois; Pietrement, Christine; et al. (Kidney international, 2017)
C3 Glomerulopathies, which include Dense Deposit Disease and C3 Glomerulonephritis, are associated with genetic and acquired dysregulation of the C3 convertase alternative pathway of complement. The potential role of the activation of the C5 convertase has not been studied extensively. Here we analyzed IgG samples from patients with C3 Glomerulopathies to identify circulating autoantibodies that stabilize the C3 alternative pathway (C3 Nephritic Factors) as well as C5 convertases (C5 Nephritic Factors), thus preventing decay of these enzyme complexes. Rare variants in alternative pathway genes were found in 28 of 120 tested patients. C3 and C5 Nephritic Factors were found in 76 of 101 (75%) and 29 of 59 (49%) of the patients, respectively. Therefore, we compared the results of the assays for the C3 and C5 nephritic factors functional activity: 29% were positive for C3 Nephritic Factors alone, 39% were positive for both C3 and C5 Nephritic Factors, and 10% were positive for C5 Nephritic Factors alone. We found that the addition of properdin-enhanced stabilization of C3 convertase in the presence of IgG doubly positive for both Nephritic Factors, while it did not modify the stabilization mediated by IgG solely positive for C3 Nephritic Factors. Both C3 and C5 Nephritic Factors correlated with C3 consumption, while only C5 Nephritic Factors correlated with sC5b9 levels. C5 Nephritic Factors-positive patients were more likely to have C3 Glomerulonephritis than Dense Deposit Disease. Thus, dysregulation of the C5 convertase contributes to C3 Glomerulopathies inter-disease differences and may have direct therapeutic implications.